Development of Plantae Accompanied by Nash (Plantaenash) Learning Model Based-on Science Literacy to Foster Integrative Thinking Skills - Sa'idah, Nailiya; Isnaeni, Wiwi; Retnoningsih, Amin (Universitas Negeri Semarang, 2022)
The learning model that combines nash (al-Quran and hadith) with Plantae subjects was developed by the teacher to train integrative thinking’s students. This research was aimed to develop a Plantae learning model accompanied by nash (Plantaenash) oriented to scientific literacy to foster students' integrative thinking skills. Integrative thinking skilis in the form of the ability to apply knowledge from various disciplines and contexts into real situations and the ability to analyze. This research method is Research and Development (R & D). The learning model was developed on the basis of needs analysis and particular literature reviews. The research product is a learning model with a teacher's guide sheet. Validity of the products was assessed by experts and teachers with an average score of 85.93% which was classified as